International workshop on biotechnology in agriculture : evolving a research agenda for the ICGEB, September, 17-22, 1985 - Natesh, S.; Chopra, V. L.; Ramachandran, S., 1934-; United Nations Industrial Development Organization; India. Department of Science and Technology; International Workshop on Biotechnology in Agriculture: Evolving a Research Agenda for the ICGEB (1985 : New Delhi, India) (New Delhi : Oxford & IBH Pub. Co., 1987)
On plant molecular biology and biotechnology.
Papers presented at the International Workshop on Biotechnology in Agriculture: Evolving a Research Agenda for the ICGEB, New Delhi, 1985; organized by United Nations Industrial Development Organization and Dept. of Science and Technology, India.
Includes bibliographies.
Keywords: Plant biotechnology -- Congresses; Agricultural biotechnology -- Congresses